2020
DOI: 10.1186/s40729-019-0202-6
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional finite element analysis of extra short implants focusing on implant designs and materials

Abstract: Aim: When using short implants, fracture of the implant body and bone resorption are a concern because stress concentrates on and around a short implant. The purpose of this research is to investigate the differences in stress distribution between tissue level (TL) and bone level (BL) implant body designs, and between commercially pure titanium (cpTi) and the newer titanium-zirconium (TiZr) alloy in using short implants. Materials and methods: Models of TL and BL implants were prepared for three-dimensional fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 41 publications
1
13
1
2
Order By: Relevance
“…A similar situation was found in the research of Araki et al [ 34 ], with a greater stress concentration on the cortical bone around the neck of the implants, although this study was performed with shorter dental implants than those used in the present work. Herekar et al [ 35 ] and Baggy et al [ 36 ] also observed higher von Mises stress values located at cervical cortical bone regions adjacent to the implants for different implant types.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…A similar situation was found in the research of Araki et al [ 34 ], with a greater stress concentration on the cortical bone around the neck of the implants, although this study was performed with shorter dental implants than those used in the present work. Herekar et al [ 35 ] and Baggy et al [ 36 ] also observed higher von Mises stress values located at cervical cortical bone regions adjacent to the implants for different implant types.…”
Section: Discussionsupporting
confidence: 87%
“…Contrary to the present work, Araki et al [ 34 ] reported a higher von Mises stress distribution in bone for bone-level and tissue-level implants; however, they used other implant types and focused on extra short implants in their study.…”
Section: Discussioncontrasting
confidence: 76%
“…The finite element analysis (FEA) has been widely used in implant dentistry to evaluate the effect of both biomechanical and clinical factors on implant success. This analysis identifies stresses and displacements on the prosthesis-implant-bone complex which can be unachievable for other biomechanical methods [41][42][43]. Therefore, in this study, FEA was used to compare the stress distribution of different glass ceramics and the effect of veneering on the prosthesis-implant-bone complex.…”
Section: Discussionmentioning
confidence: 99%
“…Young's Modulus (GPa) A series of TiZr alloys were compared with cp-Ti. The TixZr alloys with Zr content ranging from 5% to 85% were characterized [22][23][24] in terms of stress distribution, surface topography at the micro-level, electrochemical stability in a simulated oral cavity environment, in vitro cell cultures, and pre-clinical and clinical studies. Fracture of the implant body and bone resorption caused by stress around implants were investigated by finite element method, and clinical investigations concluded that the narrow-diameter TiZr implants present similar success rates and peri-implant bone resorption as cp-Ti implants of comparable dimensions [24].…”
Section: Methodsmentioning
confidence: 99%